Stock Price dan COVID-19 : Sebuah Studi Perbandingan pada Sektor Perbankan Indonesia - Elliv Hidayatul Lailiyah; Arfiana Dewi; Rita Nataliawati (JURNAL AKUNTANSI, EKONOMI dan MANAJEMEN BISNIS, 2021)
The COVID-19 pandemic has had an impact on every sector of life, including the world of capital markets and banking. This study aims to analyze the events of the COVID-19 pandemic on stock prices. This study uses a comparative study by comparing the stock prices of banks into three periods. The comparison period used is before COVID-19 hit Indonesia, when the first case of COVID-19 was announced in Indonesia (t+1) and after the first case, when the COVID-19 vaccine was first discovered (t+1). This study uses banks listed on the Indonesia Stock Exchange with the top ten largest assets in the first quarter of 2020. Data analysis uses the Paired Samples T-Test. The results of the study show that there are differences in stock prices before COVID-19 hit Indonesia and during the first case of COVID-19; there is a difference in stock prices when the first case of COVID-19 was announced in Indonesia and after the first case of COVID-19; and there is a difference in stock prices before COVID-19 hit Indonesia and after the first case of COVID-19 was announced in Indonesia.